SISTEM KOMUNIKASI PEMERINTAH DAN KOMPLEKSITAS IKON KAMBING PE DI KABUPATEN PURWOREJO - Tatag Handaka; Hermin Indah Wahyuni; Endang Sulastri; Paulus Wiryono (Jurusan Ilmu Komunikasi UTM, 2016)
ABSTRACTEttawa Crossbred (EC) goat farming in Purworejo regency dated back to the era of Dutch colonial government. The Ministry of Farming was decided that EC as Purworejo’s local crossbred. But the farmers judge that EC not to be Purworejo’s icon. The farmers was judged that government not seriousmade EC as Purworejo’s icon. The aim of this research was to know how the government communicationsystem produce and reproduce information to solve EC as Purworejo’s icon. The theory used in thisresearch is communication system in the perspective of Niklas Luhmann. The research method used wasexplorative case study. Population of this study was conducted in Purworejo regency as the center ofEC goat farming. The result of the study shows that government communication system was producedinformation in encountering the environmental complexity of EC as Purworejo’s icon. The informationabout statue of EC as signifier. Government communication system wasn’t produced the icons like ECproducts and gifts. The farmers was judged that government not serious to solved EC as Purworejo’icon. The farmers through farmers group was produced icons like EC’s signifier and EC’s products (milkpowder, caramel, yoghurt, and crackers).Keywords: government communication system, complexity, icon.